MOVIE IN ENHANCING STUDENTS’ VOCABULARY - Geminastiti Sakkir; Usman M (Makassar State University, 2018)
This research aims at finding out whether or not the use of movie is effective in enhancing the vocabulary achievement and finding out the students’ interest toward the use of movie. The research employs a pre-experimental research method. The population of this research is all the eighth grade students of SMP Negeri 2 Panca Rijang in academic year 2017/2018. The samples consist of 20 students was taken based on random sampling technique. The research data are collected using vocabulary test which is analyzed by descriptive and inferential statistics. The research result indicates that the use of movie is more effective in enhancing vocabulary achievement of the eighth grade students of SMP Negeri 2 Rappang in academic year 2017/2018. The students’ result of posttest is higher than the students’ result of pretest (80 > 70. 625). The difference of those mean score is statistically significant; it is based on t-test value at significant level 0.05, the t- table is lower than t- test (2. 093 < 3. 54).